AN ANALYSIS ON STUDENTS’ PERCEPTION ON MICROSOFT TEAMS AS A PLATFORM FOR READING COMPREHENSION - Ari Oktaviani Vani; Urai Salam; Surmiyati (JEELL (Journal of English Education, Linguistics and Literature), 2024)
This research aims to investigate the students’ perception of using Microsoft Teams for reading comprehension. There were 153 eleventh grade students at SMK Kristen Immanuel II Sungai Raya who participated in this research. This is descriptive research with a quantitative approach that used twenty-two items questionnaire as the data collection for the close-ended questions. The result presented that mostly the percentage of each aspect showed a positive response. Those were, the highest percentage strongly agree and agree of easy access to Microsoft Teams is 86,2%, perceived usefulness in Microsoft Teams is 76,59%, attitude towards use Microsoft Teams is 69,3%, behavior intention of English through using Microsoft Teams is 90,2%, and actual use of Microsoft Teams is 77,1%. According to the finding and discussion of the research, the researcher concluded that the students had a positive perception towards the use of Microsoft Teams for learning English.  The writer concluded that the students had a positive perception towards the used of Microsoft Teams for reading comprehension.